Development of a 2D Game for Training Kindergarten Children’s Survival Skills - ทองมี จุติเดช (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to develop a 2D game for survival skills training for Kindergarten children. The primary objectives were: 1) to develop the 2D survival skills training game, and 2) to evaluate children’s satisfaction with the developed game. The sample group consisted of 30 kindergarten students. The research instruments included the 2D survival training game, an expert evaluation form, and a student satisfaction questionnaire. Data were analyzed using percentage, mean, and standard deviation. The results indicated that the students’ satisfaction with the 2D survival skills training game was at the highest level, with an overall mean of 4.55. This high level of satisfaction may stem from the game’s ability to effectively illustrate survival scenarios, thereby promoting active learning. Furthermore, the 2D game format simplified complex survival skills, making them more accessible and engaging for young learners, while stimulating their desire to learn through computer-based gameplay.